2014
DOI: 10.1155/2014/765856
|View full text |Cite
|
Sign up to set email alerts
|

Cr(VI) Removal from Aqueous by Adsorption on Amine-Functionalized Mesoporous Silica Prepared from Silica Fume

Abstract: Amino-functionalized mesoporous silica MCM-41 materials have been prepared to develop efficient adsorbents of Cr(VI) in wastewater, using silica fume as silica source. Functionalization with amino groups has been carried out by using grafting method. The materials have been characterized by means of X-ray diffraction (XRD), nitrogen (N2) adsorption-desorption, Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray photoelectron spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 23 publications
(22 reference statements)
1
17
0
Order By: Relevance
“…Especially, the content of -NH 3 + is proportional to the adsorption amount of Cr(VI) by considering the XPS and Cr removal experiments. Several studies have reported that anionic Cr(VI) is adsorbed by NH 3 + groups via electrostatic interaction 14 , 32 , 33 .…”
Section: Resultsmentioning
confidence: 99%
“…Especially, the content of -NH 3 + is proportional to the adsorption amount of Cr(VI) by considering the XPS and Cr removal experiments. Several studies have reported that anionic Cr(VI) is adsorbed by NH 3 + groups via electrostatic interaction 14 , 32 , 33 .…”
Section: Resultsmentioning
confidence: 99%
“…The molecular structure of composites was investigated by FTIR technique. Figure 1 [54]. In comparison to the MCM-41 spectrum, the spectrum of MCM-41-CIP presented additional bands at 1715 cm −1 , 1494 cm −1 , and 1459 cm −1 , which were also observed in the spectrum of freeze-dried CIP confirming the drug adsorption onto the MCM-41.…”
Section: Molecular Structurementioning
confidence: 74%
“… adsorbent q max /(mg g −1 ) pH initial concentration (mg l −1 ) ref. Fe(III)-CBs 166.3 6.0 20.0 this study γ-Fe 2 O 3 -chitosan beads 106.5 5.0 1000 [ 32 ] magnetic chitosan nanoparticles 55.8 3.0 180 [ 33 ] composite chitosan biosorbent 153.8 2.0 400 [ 18 ] ethylenediamine-modified cross-linked magnetic chitosan resin 51.8 2.0 100 [ 35 ] cross-linked chitosan-Fe(III) complex 148.4 4.8 380 [ 36 ] metal ion imprinted chitosan resin 76.9 5.5 100 [ 37 ] Fe 0 nanorods modified with chitosan 118.8 5.0 200 [ 15 ] zirconium cross-linked chitosan composite 175.0 5.0 30...…”
Section: Resultsmentioning
confidence: 99%
“…Among them, adsorption has been recognized as an economical and effective technique, and much attention has been paid to the development of cost-effective and efficient adsorbents [ 11 13 ]. Various adsorbents, such as active carbon [ 14 ], silica-gel [ 15 ], raw clays [ 16 ] and hydrotalcite [ 17 ], have been used for Cr(VI) adsorption. However, these adsorbents focused on treating industrial wastewater; although they had high adsorption capacities under acid pH, the treated water still had Cr(VI) anion, whose concentration was not low as expected, limiting their broad application.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation